Unemployment and Crime: Toward Resolving the Paradox - Kapuscinski, Cezary A. (Journal of quantitative criminology, 1998)
While official crime statistics from many countries show that unemployed people have high crime rates and that communities with a lot of unemployment experience a lot of crime, this cross-sectional relationship is very often not found in time-series studies of unemployment and crime. In Australia there have been no individual-level or cross-sectional studies of unemployment and adult crime which have failed to find a positive relationship and no time-series which have supported a positive relationship. Consistent with this pattern, a time series of homicide from 1921 to 1987 in Australia reveals no significant unemployment effect. A theoretical resolution of this apparent paradox is advanced in terms of the effect of female employment on crime in a partriarchal society. Crime is posited as a function of both total unemployment and female employment. When female employment is added to the model, it has a strong positive effect on homicide, and unemployment also assumes a strong positive effect.